Empowerment of Household Women Joined in The Mandiri Women Group in The New Normal Era in Bandar Labuhan Village, Tanjung Morawa District, Deli Serdang District - Dalimunthe, Ritha Fatimah (Talenta Publisher, 2020)
Housewives who are members of the women's community can minimize the impact of the Corona 19 Virus by empowering women through training and mentoring activities to make changes in lifestyle or lifestyle so that they become housewives who understand what it means about working and doing business from home, as well as maintaining distance, living healthy and communicate online. This activity also introduces the use of yardland to optimize housewives as human resources in empowering family-based housewives. Housewives, if trained and accompanied, can be at the forefront of maintaining and providing understanding for the family. This can be done through training and mentoring for housewives who are members of the 9 independent women's community groups in Bandar Labuhan Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra who will become cadres for members. other communities or interested housewives. Then from the students, 2 people were chosen to be trained to be motivators.